Anatomical research on the funiculus umbilicalis in zebu cattle - Ribeiro, Antonio Augusto Coppi Maciel; Miglino, Maria Angélica; Didio, Liberato João Afonso (Brazilian Journal of Veterinary Research and Animal Science, 1997)
Morphologic aspects related to disposition and constitution of arteries and veins of the umbilicus funiculus were investigated in 30 (13 males and 17 females) fetuses of crossbred zebu cattle. The age of the fetuses varied in a range of 2 to 7 months, and the umbilical vessels were injected with a “650” Neoprene latex solution, properly stained and then dissected. Additionally to this procedure, the umbilicus funiculus were cut at the juxta-fetal, juxta-placental and at the intermediate portions and werestudied histologically by means of different staining techniques. The length of the umbilical cord varied from 3 to 43 cm in fetuses 2 to 7 months old. The umbilicus funiculus of the animals studied was constituted by 4 umbilical vessels, i.e., 2 arteries and 2 veins, and by one alantoid duct, and among these formations a large amount of Wharton gelatinous substances and small essels (vasa vasorum) were observed. All these strctures were involved by the amniotic epithelium. Inter-aterialumbilical anastomoses were found in 28/30 (93,33%) of the examined animals.